Automatic temporal lobe atrophy assessment in prodromal AD: Data from the DESCRIPA study. Issue 4 (16th September 2013) - Chincarini, Andrea; Bosco, Paolo; Gemme, Gianluca; Esposito, Mario; Rei, Luca; Squarcia, Sandro; Bellotti, Roberto; Minthon, Lennart; Frisoni, Giovanni; Scheltens, Philip; Frölich, Lutz; Soininen, Hilkka; et al.
Abstract: Background: In the framework of the clinical validation of research tools, this investigation presents a validation study of an automatic medial temporal lobe atrophy measure that is applied to a naturalistic population sampled from memory clinic patients across Europe. Methods: The procedure was developed on 1.5‐T magnetic resonance images from the Alzheimer's Disease Neuroimaging Initiative database, and it was validated on an independent data set coming from the DESCRIPA study. All images underwent an automatic processing procedure to assess tissue atrophy that was targeted at the hippocampal region. For each subject, the procedure returns a classification index. Once provided with the clinical assessment at baseline and follow‐up, subjects were grouped into cohorts to assess classification performance. Each cohort was divided into converters ( co ) and nonconverters ( nc ) depending on the clinical outcome at follow‐up visit. Results: We found the area under the receiver operating characteristic curve (AUC) was 0.81 for all co versus nc subjects, and AUC was 0.90 for subjective memory complaint (SMC nc ) versus all co subjects. Furthermore, when training on mild cognitive impairment (MCI ‐nc /MCI ‐co ), the classification performance generally exceeds that found when training on controls versus Alzheimer's disease (CTRL/AD). Conclusions: Automatic magnetic resonance imaging analysis may assist clinical classification of subjects in a memory clinic setting even when images are not specifically acquired for automatic analysis.